INVESTIGATION OF STRUCTURE OF INDIVIDUAL-TYPOLOGICAL PERSONALITY IN PATIENTS WITH ALCOHOLISM AND LUDOMANIA. - Аймедов, Костянтин Володимирович; Лобасюк, Борис Олександрович; Боделан, Максим Іванович (Psychiatry, Neurology and Medical Psychology, 2018)
The aim of the study was to detect regression (multiple linear regression and correlation) and correlation (two-dimensional correlation method) relationships between the indicators of Kettel’s test in mentally ill with addictive disorders (alcoholics and ludomanes). For the formation of mathematical models, each of the indicators of the set selected in the analysis, was considered as the target sign (Y), and the other elements of the set as X and the method of multiple linear regression determined orientated influences. As a result of the procedure used, we obtained the equation of multiple linear regression. The adequacy of the regression coefficients was estimated by the method of sigma deviations of the regression coefficients, and the efficiency of the regression as a whole was estimated by means of calculating the multiplier correlation coefficient. Geometrically, the equation of multiple linear regression was interpreted using polycyclic multigraphs.Between the factors of the Kettle test in the mentally healthy participants of the study, there were more oriented statistically significant regression relationships-ratios than those suffering from alcoholism and ludomania. The coefficients of the two-dimensional correlation between the indicators of Kettle’s test in people suffering from alcoholism and ludomania appeared to be more than healthy ones. In the established system of indexes of Kettel’s tests, system-forming, depending on the research group, the following factors-indicators were determined: in the conditions of the psychological norm - restraint-expressiveness and low intelligence-high intelligence; among patients with alcoholism - alaaxia-protense (trust, openness-suspiciousness, jealousy); among patients suffering from ludomanii - low super-his-high super-him and trektia - parmy (timidity, indecision, courage, entrepreneurship). The discrepancies of system-forming factors are revealed, which testify that in the course of chronic alcoholism and ludomania the formation of orientation on the lower levels of the value system appears. The obtained mathematical models visualize the destruction of mental activity in persons suffering from alcoholism and ludomania.